2020
DOI: 10.1016/j.amsu.2020.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Reported burnout among U.S. general surgery residents: A survey of the association of program directors in surgery members

Abstract: Introduction The literature remains unclear on the development, consequences, and interventions for burnout in resident populations. We aim to identify the prevalence and nuances of reported burnout in general surgery resident physicians to better understand which factors contribute the greatest risk. Methods A 42-question anonymous online survey was distributed by the Association of Program Directors in Surgery (APDS) to general surgery resident physicians. ANOVA, chi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 18 publications
(21 reference statements)
1
23
0
Order By: Relevance
“…Overall, the study showed that CRAs' job burnout was very serious, and was dominated by emotional exhaustion and depersonalization (76.7% and 65.5%, respectively, of those surveyed), both of which were higher than that reported for jobs in any other eld [29][30] , but similar with the job burnout survey in the clinicians [31][32][33] .…”
Section: Discussionmentioning
confidence: 64%
“…Overall, the study showed that CRAs' job burnout was very serious, and was dominated by emotional exhaustion and depersonalization (76.7% and 65.5%, respectively, of those surveyed), both of which were higher than that reported for jobs in any other eld [29][30] , but similar with the job burnout survey in the clinicians [31][32][33] .…”
Section: Discussionmentioning
confidence: 64%
“…Among US general surgery residents, females were 2.7 times more likely to report burnout and nearly twice as likely to report contemplating suicide compared to males [47]. A different study that observed higher negative impact on women attributed the effect size to extraneous influences beyond gender [56].…”
Section: Gendermentioning
confidence: 89%
“…Among 81 US general surgery residents, 89.5% of university-hospital affiliated and 95.2% of community teaching hospital affiliated residents attested to burnout. After adjustment, those at community centers showed a nearly fifteen times greater likelihood of burnout [47].…”
Section: Locationmentioning
confidence: 98%
See 2 more Smart Citations